Functional analysis and interaction networks of Rboh in poplar under abiotic stress - Wang, Jing; Liu, Xiaojiao; Kang, Yude; Liu, Aizhong; Li, Ping (Frontiers in Plant Science, 2025)
IntroductionPlant respiratory burst oxidase homologs (Rbohs) are essential in the generation of reactive oxygen species (ROS) and play critical roles in plant stress responses. Despite their importance, Rbohs in poplar species remain under-explored, especially in terms of their characteristics and functional diversity across different species within the same genus.MethodsIn this study, we employed bioinformatics methods to identify 62 Rboh genes across five poplar species. We analyzed the gene structure, physical properties, chromosomal distribution, and cis-elements. Additionally, we used qRT-PCR to examine the expression of PyRbohs (Populus yunnanensis Rbohs) under various stress treatments and yeast two-hybrid (Y2H) assays to confirm interactions with calcium-dependent protein kinases (CPKs).ResultsAll identified Rboh genes consistently contained six conserved functional domains and were classified into four distinct groups (I-IV). The number of Rboh members across poplar species was consistent with evolutionary patterns. These Rbohs exhibited relatively conserved amino acid lengths (832-989) and shared basic protein characteristics, including cell membrane localization. Chromosomal distribution analysis revealed an uneven distribution of PyRbohs across chromosomes, with abundant collinearity pairs among different plant species, indicating tandem segment duplications and a shared evolutionary origin within group members. Cis-element analysis identified stress-responsive and hormone signaling-related elements. qRT-PCR demonstrated the upregulation of PyRbohs under salt, drought, PEG, and ABA treatments. Protein interaction predictions using the STRING database identified potential functional mechanisms of PyRbohs, including interactions with CPKs. Y2H assays confirmed the interaction between PyRbohs and CPKs, suggesting that CPK binding might regulate PyRboh activity and ROS production.DiscussionOverall, these findings provide a comprehensive understanding of the evolutionary, structural, and functional diversity of poplar Rbohs. They highlight promising candidate genes for enhancing stress tolerance in poplar species and lay a foundation for future research on the molecular mechanisms underlying Rboh-mediated stress responses in poplar.